Detections of far-infrared [OIII] and dust emission in a galaxy at z = 8.312: Early metal enrichment in the heart of the reionization era. Issue Volume 15:Issue S341(2019) (November 2019) - Tamura, Y.; Mawatari, K.; Hashimoto, T.; Inoue, A. K.; Zackrissonm, E.; Christensen, L.; Binggeli, C.; Matsuda, Y.; Matsuo, H.; Takeuchi, T. T.; Asano, R. S.; Sunaga, K.; et al.
Abstract: We present ALMA detection of the [O iii ] 88 μ m line and 850 μ m dust continuum emission in a Y -dropout Lyman break galaxy, MACS0416_Y1. The [O iii ] detection confirms the object with a spectroscopic redshift to be z = 8.3118±0.0003. The 850 μ m continuum intensity (0.14 mJy) implies a large dust mass on the order of 4×10 6 M ⊙ . The ultraviolet-to-far infrared spectral energy distribution modeling, where the [O iii ] emissivity model is incorporated, suggests the presence of a young (τage ≍ 4 Myr), star-forming (SFR ≍ 60 M ⊙ yr −1 ), and moderately metal-polluted ( Z ≍ 0.2 Z ⊙ ) stellar component with a stellar mass of 3 × 10 8 M ⊙ . An analytic dust mass evolution model with a single episode of star formation does not reproduce the metallicity and dust mass in ≍ 4 Myr, suggesting an underlying evolved stellar component as the origin of the dust mass.